The Influence of Leadership Style and Remuneration System on Improving Individual Performance of Central General Hospital Employees Dr. Sitanala Tangerang with Work Culture as an Intervening Variable - Deny Erfin; Arrozi Adhikara; Anastina Tahjoo (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2024)
To produce employees who have good quality and have a professional attitude, it is necessary to carry out good management, in order to increase the company's economic resources. Previously reported by RSUP Dr. Sitanala has a leader with a leadership style where all provisions are based on the leadership's provisions, optimizing public stigma regarding leprosy-oriented services that have not reached the expected target, a lack of visits which has an impact on the remuneration system being less than optimal, performance indicator values ​​that have not reached the target, lack of Community satisfaction is still relatively high in the community satisfaction index survey. The aim of this research is to analyze the influence of leadership style and remuneration systems on improving employee performance at RSUP Dr. Sitanala Tangerang with work culture as an intervening variable. Research method the research design used was a survey with an explanatory causality approach. The population used is all employees who have the status of Civil Servants (PNS) at RSUP Dr. Sitanala, numbering 340 people. The sample in this study amounted to 183 people, the sampling technique used was accidental sampling. There is a direct and significant influence between leadership style and remuneration on work culture, there is an indirect influence of leadership style on employee performance, there is a direct influence of remuneration on employee performance, work culture directly has a significant influence on improving performance and the remuneration system has a direct influence towards improving performance without going through work culture. For hospitals, hospital leaders should always monitor each work unit both from an objective and subjective performance perspective as well as from the individual employee perspective so that they can find out directly what the obstacles, complaints and needs of individual employees are in carrying out teamwork in each work unit at once. can control the continuity of performance of each individual employee as a work culture within the team in the unit so that it is hoped that organizational goals will be achieved optimally. For other researchers: It is hoped that further research can further analyze other aspects and influences that can achieve organizational goals with a wider range of respondents. There are still many other aspects and influences that could possibly be used as research targets for development at the hospital in question.